2011
DOI: 10.1016/j.febslet.2011.04.066
|View full text |Cite
|
Sign up to set email alerts
|

How do immune cells overcome the blood–brain barrier in multiple sclerosis?

Abstract: Keywords:Blood-brain barrier Multiple Sclerosis Leukocyte Cytokine Reactive oxygen species Matrix metalloproteinase a b s t r a c tThe presence of the blood-brain barrier (BBB) restricts the movement of soluble mediators and leukocytes from the periphery to the central nervous system (CNS). Leukocyte entry into the CNS is nonetheless an early event in multiple sclerosis (MS), an inflammatory disorder of the CNS. Whether BBB dysfunction precedes immune cell infiltration or is the consequence of perivascular leu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
266
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 327 publications
(275 citation statements)
references
References 209 publications
7
266
0
2
Order By: Relevance
“…In particular, disrupted occludin expression and distribution have been reported within the microvascular endothelium of patients with MS (27), clearly paralleling our findings in AnxA1 −/− mice and AS hCMEC/D3 clones. It is important to note that endothelial ANXA1 down-regulation occurs in normal-appearing white matter, a finding that may inform the extensive discussion whether deficits in BBB permeability precede leukocyte extravasation or are a consequence of immune cell accumulation (28). In particular, our finding that ANXA1 down-regulation occurs at sites distant from active lesions strongly suggests a preexisting weakening of BBB integrity before leukocyte extravasation and the development of active demyelination.…”
Section: Discussionmentioning
confidence: 81%
“…In particular, disrupted occludin expression and distribution have been reported within the microvascular endothelium of patients with MS (27), clearly paralleling our findings in AnxA1 −/− mice and AS hCMEC/D3 clones. It is important to note that endothelial ANXA1 down-regulation occurs in normal-appearing white matter, a finding that may inform the extensive discussion whether deficits in BBB permeability precede leukocyte extravasation or are a consequence of immune cell accumulation (28). In particular, our finding that ANXA1 down-regulation occurs at sites distant from active lesions strongly suggests a preexisting weakening of BBB integrity before leukocyte extravasation and the development of active demyelination.…”
Section: Discussionmentioning
confidence: 81%
“…The results of our study corroborate other findings where exercise produced an immunomodulatory effect, by reducing the pro-inflammatory and increasing the anti-inflammatory cytokines (Souza et al 2016). Production of TNF-α directly affects the BBB permeability (Larochelle et al 2011). Evidence has shown that physical exercise inhibited the production of pro-inflammatory cytokines, upregulated the regulatory T cells, and suppressed IL-6 and TNF-α production associated with the inhibition of adhesion molecules and reestablishment of tight junction protein expression, thereby restraining BBB permeability (Mota et al 2012, Souza et al 2016.…”
Section: Discussionmentioning
confidence: 99%
“…B cells are also essential in MS immunopathogenesis, as antibodies produced within the CNS are a fundamental feature of the disease (i.e., oligoclonal bands) and as B-cell-directed therapies provide strong protection against lesion formation. It is clear that during immune cell infiltration and lesion formation, BBB function becomes compromised (Larochelle et al 2011), which is characterized by vascular leakage associated with alterations of junctional proteins. Analysis of MS tissue shows that abnormalities in the expression of junctional proteins coincide with perivascular astrogliosis, and such changes are detected in very early stages of lesion formation ).…”
Section: Ms and Related Disordersmentioning
confidence: 99%